Self-care behavior mediates the relationship between health literacy and blood pressure in older adults with hypertension (Bangladesh Journal of Medical Science, 2024)
Objective To test the mediating role of self-care behavior in the relationship between health literacy and BP control in older adults with hypertension.Material and methods A cross-sectional study design was used. We enrolled 220 older adult patients with hypertension at one teaching hospital in Vietnam. Logistic regression and linear regression were conducted to test the mediation effect of self-care behavior in the relationship between health literacy and BP control.Results and discussion Self-care behavior mediated the relationship between health literacy and BP control. The significant coefficient of path a (β = 0.019, p < .001), and path c (β = -0.054, p < .001) suggested a significant effect of health literacy on self-care behavior, and a significant total effect of health literacy on BP control, while the non-significant coefficient of path b (β = -0.012, p = .577) suggested a non-significant effect of self-care behavior on BP control. Additionally, the significant coefficient of path c’ (β = -0.053, p < .001) suggested a mediation model, that is, self-care behavior mediated the relationship between health literacy and BP control.Conclusion Self-care behavior is observed as a mediating factor in the relationship between health literacy and blood pressure (BP) control among older adults with hypertension in Vietnam.Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 476-483